Moving Out and Up : Panel Data Evidence on Migration and Poverty in Uganda - Mensah, Edouard; O'Sullivan, Michael (World Bank, Washington, DC, 2017)
This paper examines the relationship between spatial and economic mobility in Uganda using longitudinal data from 2005 through 2012. The study relies on a detailed panel tracking survey and exploits exogenous variation in the spatial intensity of violent conflict, rainfall shocks, distance from the regional capital, and ethnic networks in urban areas. The analysis finds significant welfare gains of 58 percentage points due to migration. However, the returns to migration vary with the direction of the move. Moving to a rural destination yields welfare returns of 56 percentage points; the returns to urban moves, at 65 percentage points, are markedly higher. Policies to capture the welfare gains from migration to cities should focus on further urbanization, the development of road infrastructure, and investments in education for men and women in rural areas.